1987
DOI: 10.1128/aac.31.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose ciprofloxacin at 100 versus 250 mg for treatment of uncomplicated urinary tract infections in women

Abstract: Treatment with single doses of antibiotics of uncomplicated urinary tract infections in women is a well-established therapeutic regimen (1,4,12,15,20). Therapeutic failures following a single-dose treatment appear to predict complicating factors such as silent pyelonephritis (14), morphologic alterations, dynamic disturbances, or microbial resistance to antibiotics (6,8,11,13).Ciprofloxacin, a new'quinolone drug which can be administered both orally and intravenously, has good antimicrobial activity against mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Recent uncontrolled studies in women with uncomplicated cystitis have shown cure rates 4 weeks after treatment with ciprofloxacin 100-and 250-mg single-dose regimens of 74 to 79% (7) and with 250-and 750-mg single-dose regimens of 64 to 70% (19). Similar to our experience, only two of four infections caused by S. saprophyticus were cured in one study (7). Ofloxacin in a 100-mg single-dose regimen resulted in an 80% cure rate 4 weeks after treatment in one uncontrolled study (18) and an 86% cure rate in another study with an unstated follow-up interval (13).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Recent uncontrolled studies in women with uncomplicated cystitis have shown cure rates 4 weeks after treatment with ciprofloxacin 100-and 250-mg single-dose regimens of 74 to 79% (7) and with 250-and 750-mg single-dose regimens of 64 to 70% (19). Similar to our experience, only two of four infections caused by S. saprophyticus were cured in one study (7). Ofloxacin in a 100-mg single-dose regimen resulted in an 80% cure rate 4 weeks after treatment in one uncontrolled study (18) and an 86% cure rate in another study with an unstated follow-up interval (13).…”
Section: Resultssupporting
confidence: 79%
“…We also studied the effects of these regimens on rectal and perineal colonization with coliforms. * 7 days. The patients were asked to return 2 to 3 days after enrollment (early follow-up visit), 5 to 9 days after treatment (1-week posttreatment visit), and 4 to 6 weeks after treat-ment (5-week posttreatment visit).…”
mentioning
confidence: 99%
“…However, fluoroquinolones appear to be highly efficient given as a 3-day regimen. Hooton et al (4) Two previous studies showed lower cure rates when a single-dose ciprofloxacin (2) or ofloxacin (4) was given to women with Staphylococcus saprophyticus bacteriuria. In our study, one of two women with S. saprophyticus bacteriuria treated with cefixime and all three women treated with ofloxacin failed.…”
mentioning
confidence: 99%
“…For other antimicrobial agents effective as short courses of therapy, 3 days of therapy has been suggested to be appropriate (6,8,9,16). For the fluoroquinolone antimicrobial agents, in particular, 3 days of therapy seems necessary because of the high failure rates of single-dose therapy of infection with Staphylococcus saprophyticus, the second most frequent infecting organism in this syndrome (5,8,17). In Canada, norfloxacin has been marketed with an indication for 3 days of therapy for uncomplicated urinary tract infections, making it the only antimicrobial agent marketed with an indication for a short course of therapy for this syndrome.…”
mentioning
confidence: 99%